Impact of COVID-19 pandemic on pharmaceutical systems and supply chain - a phenomenological study - Tafadzwa Tirivangani, BPharm; Bertha Alpo, BPharm; Dan Kibuule, BPharm; MSc; PhD; Johannes Gaeseb, BPharm; MPH; Babafunso A. Adenuga, BPharm; MPH; PhD (Elsevier, 2021)
Background: Resilient pharmaceutical systems and supply chains are critical in the control of COVID-19, a pandemic that has mostly devastated public health systems and livelihoods in resource-limited countries in sub-Saharan Africa. Objective: To evaluate the impact of COVID-19 on pharmaceutical systems and supply chain in a resource-limited setting. Methods: A descriptive qualitative survey using a phenomenological approach was conducted among key informants in the public and private pharmaceutical sectors of Namibia. Data were collected on the perceived impact of COVID-19 pandemic on the supply chain, as well as access and availability of essential medicines among the distributors and points of care in the private and public sectors. Qualitative themes of the impact were analyzed using Tesch's approach. Results: Of the 21 key-informants, 57.1% were female and 85% were from the private versus the public pharmaceutical sector. Overall, key informants reported a negative impact on access and availability of essential medicines, particularly sanitation and hygiene products, and antimicrobials. Most medicine outlets, experienced longer lead times, attributed to reduced inter-country transportation of goods and services and limited in-country capacity and capabilities to manufacture. The main thematic challenges included bureaucratic bottlenecks and lack of emergency readiness of the medicine's logistics supply chain in Namibia. Conclusion: COVID-19 pandemic aggravated the inequitable access to essential medicines in the public and private sectors of Namibia. Governments in resource-limited countries need to strengthen in-country Private-Public Partnerships as well as regional treaties for Universal Health Coverage in context of the COVID-19 pandemic.